What made Lebanese emigrant nurses leave and what would bring them back? A cross-sectional survey. (March 2020) - Alameddine, Mohamad; Kharroubi, Samer A.; Dumit, Nuhad Y.; Kassas, Sara; Diab-El-Harake, Marwa; Richa, Nathalie
Abstract: Background: The nursing workforce is critical for the provision of quality health-care and positive patient outcomes. There is a global trend of migration of nurses from under-developed to developed countries due to attractive job offers in the host countries. Lebanon presents such a case where nurses are migrating abroad, leading to shortages in the nursing workforce in their home country. Objectives: The aim of this study was to investigate reasons for the migration of Lebanese nurses, and incentives that would attract them back to their home country in order to enhance the nursing workforce in Lebanon. Design: This study is a cross-sectional survey of emigrant Lebanese nurses. Settings: Recipient countries where Lebanese nurses emigrated. Participants: 440 Emigrant Lebanese nurses were identified through the registration database of the Order of Nurses in Lebanon. The survey was sent to all of them via email; 153 responses were received. Methods: Data were collected from November 2017 to March 2018. Analysis included univariate and bivariate tests to present descriptive statistics of the respondents, and to examine region of residence and gender in relation to their current job satisfaction, reasons for leaving Lebanon, intention to return to Lebanon, and aspects that would attract them back to their home country. Logistic regression analysis was used to determine the socio-demographic and work-related characteristics associated with the odds of returning to practice nursing in Lebanon. Results: A total 136 completed responses were considered. Emigrant Lebanese nurses were highly educated, with more years of work experience, and older than nurses remaining in their home country. Top reasons for nurses to leave Lebanon included unsatisfactory salary or benefits, better work opportunities in other countries, and lack of professional development or career advancement. The majority of surveyed nurses (59%) expressed willingness to return to practice nursing in Lebanon. Aspects that would attract emigrant Lebanese nurses back to their home country include attractive salary or better benefits and opportunities for professional development, career advancement, or continuing education. Emigrant Lebanese nurses residing in the Gulf, staff nurses, and nurses with more years of work experience were more likely to return to practice nursing in Lebanon. Conclusion: Highly educated and experienced nurses are departing from Lebanon. This presents a challenge for the less experienced nurses remaining in the country, who could benefit from the mentorship and experience of their migrating peers. Creating an environment that could enhance the professional development of nurses in Lebanon, with financial incentives could retain the nursing workforce in the country.